Flexible risk control strategy based on multi-stage corrective action with energy storage system. (September 2019) - Kim, S.; Lee, Y.R.; Kim, M.K.
Highlights: A risk control strategy with ESS for alleviation line overload in post-contingency is presented. This problem is formulated as a multi-stage FRC-OPF with remedy action. The multi-stage corrective action is classified into three types of STCA, MTCA, and LTCA. The risk index is obtained by different types of a piecewise linear severity function. The simulation results confirm performance and validity of proposed approach. Abstract: This paper presents a flexible risk control strategy with energy storage system to assist in taking a remedy action for removing a line overload in post-contingency. The problem is formulated as a flexible risk constrained-optimal power flow with multi-stage corrective action, which is classified into three types using the difference in ramp rate characteristics of the energy storage system unit and generator. The first-stage minimizes the operating costs in pre-contingency and the remaining stages help to mitigate the risk in post-contingency. With reference to the emergency transmission rating, each line has been set with different risk constraints. Here, the risk index is implemented by different types of a piecewise linear severity function according to the line overload. The proposed strategy can mitigate the risk constraint by taking a rapid corrective action using an storage units with a fast ramp rate, and it is proved using RTS 96 modified 24-bus and 73-bus systems. Based on the results of the case study, in which other strategies are compared, the proposed multi-stage risk control strategy with ESS is found yield a better performance.